2020
DOI: 10.1093/cid/ciaa1408
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasonography for Risk Stratification in Patients with Coronavirus Disease 2019 (COVID-19): A Prospective Observational Cohort Study

Abstract: Background Point-of-care lung ultrasound (LUS) is a promising pragmatic risk stratification tool in COVID-19. This study describes and compares LUS characteristics between patients with different clinical outcomes Methods Prospective observational study of PCR-confirmed COVID-19 adults with symptoms of lower respiratory tract infection in the emergency department (ED) of Lausanne University Hospital. A trained physician recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 30 publications
2
59
0
2
Order By: Relevance
“…Given the extensive lung involvement in COVID-19 patients, LUS may have some potential utility in the management of acutely ill patients [15,16]. Some studies have reported an improvement in lung involvement assessment in COVID-19 by using LUS in the context of ED and ICU [17,18], but we only have found two prospective studies analyzing the prognostic value of LUS during the first pandemic wave of COVID-19 (March & April 2020) [19]. The first included 80 patients (17 outpatients, 42 hospitalized and 21 with orotracheal intubation or death), initially admitted to ED.…”
Section: Discussionmentioning
confidence: 96%
“…Given the extensive lung involvement in COVID-19 patients, LUS may have some potential utility in the management of acutely ill patients [15,16]. Some studies have reported an improvement in lung involvement assessment in COVID-19 by using LUS in the context of ED and ICU [17,18], but we only have found two prospective studies analyzing the prognostic value of LUS during the first pandemic wave of COVID-19 (March & April 2020) [19]. The first included 80 patients (17 outpatients, 42 hospitalized and 21 with orotracheal intubation or death), initially admitted to ED.…”
Section: Discussionmentioning
confidence: 96%
“…LUS predicts mortality with AUC 0.72, and score ≥ 26 had 90% specificity for mortality during admission. Interestingly, two recent studies also demonstrated that LUS has a good agreement in the assessment of outcomes in COVID-19 patients: Brahier et al and Youden et al showed correlation between LUS and mortality with AUC 0.76 and 0.78, respectively [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few prospective studies demonstrating that lung ultrasound can predict outcomes in COVID-19. LUS has been strongly correlated with pulmonary involvement and provides risk stratification, including prediction of need for mechanical ventilation and mortality [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, CT plays an important role in controlling the spread of COVID-19. However, CT has some insurmountable shortcomings, such as high cost, exposure to radiation, and their immobile nature, which can be overcome by lung ultrasound (LUS) [28][29][30][31]. Coupled with the fact that the lesions of COVID-19 tend to occur in subpleural regions, LUS has been suggested as a potential triage and diagnostic tool for COVID-19 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with the fact that the lesions of COVID-19 tend to occur in subpleural regions, LUS has been suggested as a potential triage and diagnostic tool for COVID-19 [32]. The latest research showed that LUS was a promising tool for early risk stratification in COVID-19, which may guide patients' management strategies, as well as resource allocation in case of surge capacity [28,31].…”
Section: Discussionmentioning
confidence: 99%